Beliefs about inequality and the nature of support for redistribution - Aljosha Henkel; Ernst Fehr; Julien Senn; Thomas Epper (University of Zurich, Department of Economics, 2024)
Do beliefs about inequality depend on distributive preferences? What is the joint role of preferences and beliefs about inequality for support for redistribution? We study these questions in a staggered experiment with a representative sample of the Swiss population conducted in the context of a vote on a highly redistributive policy proposal. Our sample comprises a majority of inequality averse subjects, a sizeable group of altruistic subjects, and a minority of predominantly selfish subjects. Irrespective of preference types, individuals vastly overestimate the extent of income inequality. An information intervention successfully corrects these large misperceptions for all types, but essentially does not affect aggregate support for redistribution. These results hide, however, important heterogeneity because the effects of beliefs about inequality for demand for redistribution are preference-dependent: only affluent inequality averse individuals, but not the selfish and altruistic ones, significantly reduce their support for redistribution. These findings cast a new light on the seemingly puzzling result that, in the aggregate, large changes in beliefs about inequality often do not translate into changes in demand for redistribution.
Keywords: D31; D72; H23; H24; 330; Social Preferences; Beliefs about Inequality; Preferences for Redistribution; Information; Inequality Aversion